New species of the genus Cheumatopsyche Wallengren 1891 (Insecta: Trichoptera: Hydropsychidae) from Indian Himalaya - Pandher, Manpreet Singh; Malicky, Hans; Parey, Sajad H. (Zootaxa, 2018)
Three new species belonging to genus Cheumatopsyche Wallengren are described and illustrated. The newly described species are Cheumatopsyche nigrocephala sp. nov. and Ch. similis sp. nov. both from Uttarakhand, and Ch. meghalayaensis sp. nov. from Meghalaya. Cheumatopsyche guadunica Li & Dudgeon 1988 is reported for the first time from India. Cheumatopsyche ningmapa Schmid 1975 and Ch. galahittigama Schmid 1958 are also redescribed and reillustrated based on Indian specimens (males only). Due to insufficient description five species described by the Navás are considered to be nomina dubia (Cheumatopsyche chlorogastra (Navás 1932), Ch. indica (Navás 1932), Ch. lebasi (Navás 1932), Ch. stenocyta (Navás 1932), Ch. suffusa (Navás 1932). Previously, this genus was represented by 23 species and, with the addition of 3 new species and one new country record, there are now 27 species known from India.